The molecular mechanism of thrombospondin family members in cardiovascular diseases - Pan, Heng; Lu, Xiyi; Ye, Di; Feng, Yongqi; Wan, Jun; Ye, Jing (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular diseases have been identified as vital factors in global morbidity and mortality in recent years. The available evidence suggests that various cytokines and pathological proteins participate in these complicated and changeable diseases. The thrombospondin (TSP) family is a series of conserved, multidomain calcium-binding glycoproteins that cause cell-matrix and cell-cell effects via interactions with other extracellular matrix components and cell surface receptors. The TSP family has five members that can be divided into two groups (Group A and Group B) based on their different structures. TSP-1, TSP-2, and TSP-4 are the most studied proteins. Among recent studies and findings, we investigated the functions of several family members, especially TSP-5. We review the basic concepts of TSPs and summarize the relevant molecular mechanisms and cell interactions in the cardiovascular system. Targeting TSPs in CVD and other diseases has a remarkable therapeutic benefit.